Work-Related Quality of Life among Public Secondary School Teachers in the City of Manila, Philippines - Panuelos, Nil Edward; Pili, Maria Socorro (Journal of Interdisciplinary Perspectives, 2024)
This study investigates the Work-Related Quality of Life (WRQoL) among public secondary school teachers in the City of Manila, Philippines, focusing on domains such as General Well-being, Home-Work Interface, Job-Career Satisfaction, Control at Work, Working Conditions, and Stress at Work. The research aims to assess the levels of WRQoL and identify differences based on demographic profiles. A descriptive cross-sectional study was employed, involving 190 secondary public school teachers. Data were collected using a standardized WRQoL questionnaire developed by the Quality of Working Life Research Center at the University of Portsmouth. The study utilized convenience and snowball sampling methods, ensuring voluntary participation and adherence to ethical standards. Results indicate that most respondents exhibit a high quality of life, with significant differences observed in stress at work and area of specialization and age- related differences in home-work interface and working conditions. Specifically, 60% of respondents reported higher overall WRQoL, 27.5% had average, and 12.6% had low WRQoL. The study found no significant gender differences across WRQoL subscales. However, age significantly influenced the home- work interface and working conditions, with younger teachers experiencing more favorable conditions. In conclusion, the study highlights the importance of addressing occupational stress and enhancing working conditions to improve teachers' quality of life. The findings suggest that targeted interventions considering age and specialization could further enhance teachers' work-related quality of life, ultimately benefiting educational outcomes.